Peste des petits ruminants (PPR) vaccination cost estimates in Burkina Faso - Ilboudo, Guy S.; Kane, P.A.; Kotchofa, Pacem; Okoth, Edward A.; Maiga, Assoumane; Dione, Michel M. (MDPI, 2022)
Every year the government organizes country-wide vaccination campaigns targeting peste des petits ruminants (PPR) for small ruminants (sheep and goats). Despite the heavy investment in vaccination, no study has either rigorously estimated or described the cost of vaccine delivery. This study aimed to fill this gap by assessing and describing the cost of delivery of vaccines against PPR using the 2020 vaccination campaign data. The microcosting approach based on the World Health Organization (WHO) guidelines to construct comprehensive multiyear plans (cMYP) for human immunization programs was used. The cost data is presented for the public and private vaccine delivery channels separately and analyzed using three approaches considering activity lines, inputs, and nature of cost (fixed versus variable). Results show that the unit cost of vaccinating a sheep or goat is estimated at XOF 169 (USD 0.3) and XOF 103 (USD 0.18) through the public and private channels, respectively. Using the activity line framework, we found that the field activities including charges for vaccinator, cost of vaccination materials, and field transportation account for more than 50% of the vaccination cost. In terms of inputs, the personnel cost is the most significant contributor with 65%. Fixed costs are higher in the public sector with up to 46% compared to the private sector which is estimated to take 26% of the cost. This study informs veterinary services’ investment decision options for a better allocation of resources in implementing PPR and other small ruminant disease control efforts in Burkina Faso and the Sahel.